A molecular mechanism for the origin of a key evolutionary innovation, the bird beak and palate, revealed by an integrative approach to major transitions in vertebrate history. (1st July 2015) - Bhullar, Bhart‐Anjan S.; Morris, Zachary S.; Sefton, Elizabeth M.; Tok, Atalay; Tokita, Masayoshi; Namkoong, Bumjin; Camacho, Jasmin; Burnham, David A.; Abzhanov, Arhat
Abstract: The avian beak is a key evolutionary innovation whose flexibility has permitted birds to diversify into a range of disparate ecological niches. We approached the problem of the mechanism behind this innovation using an approach bridging paleontology, comparative anatomy, and experimental developmental biology. First, we used fossil and extant data to show the beak is distinctive in consisting of fused premaxillae that are geometrically distinct from those of ancestral archosaurs. To elucidate underlying developmental mechanisms, we examined candidate gene expression domains in the embryonic face: the earlier frontonasal ectodermal zone (FEZ) and the later midfacial WNT‐responsive region, in birds and several reptiles. This permitted the identification of an autapomorphic median gene expression region in Aves. To test the mechanism, we used inhibitors of both pathways to replicate in chicken the ancestral amniote expression. Altering the FEZ altered later WNT responsiveness to the ancestral pattern. Skeletal phenotypes from both types of experiments had premaxillae that clustered geometrically with ancestral fossil forms instead of beaked birds. The palatal region was also altered to a more ancestral phenotype. This is consistent with the fossil record and with the tight functional association of avian premaxillae and palate in forming a kinetic beak.